(untitled) (Altre Modernità, 2018)
The paper proposes a comparative analysis of the question of limit in its connections with the work of the Negative (Le Travail du négatif, A. Green) in two great proses of the 20th Century: Samuel Beckett’s Company (1980) and Franz Kafka’s Der Bau (The Burrow, 1923/24). The contribution articulates in two main moments: within the specificity of a psychoanalytical approach, I reconsider the problem of the Work of the Negative in literature, discussing how, in Kafka’s and Beckett’s works, the Negative represents a radical alterity to a philosophical perspective. In a second moment of the paper, I analyse the complexity of the representational strategy of the limit in Kafka’s and Beckett’s writings, investigating thus the question of subjectivity and the relationship with an Otherness through the writing, the question of memory, its construction processes by means of writing, the work of mourning, and the development of poetics of irreducibility and unrepresentability towards an ethics of literature.